Pengaruh Katekese Perkawinan Terhadap Kesiapan Emosional dan Mental Pasangan Calon Suami Istri dalam Membangun Rumah Tangga di Paroki Katedral Denpasar - Agustina Paschalia Elitawati Lamabelawa; Lidia Sandra (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Marriage is a sacred vocation that signifies a profound commitment between husband and wife, rooted in love and faith. Many couples, however, lack the emotional and mental readiness to navigate marital challenges. This study examines the impact of Pre-Marriage Catechesis (KPP) on the emotional and mental readiness of Catholic couples in the Holy Spirit Cathedral Parish, Denpasar. Using a pretest- posttest experimental design, data were collected from 89 participants (44 males, 45 females) in November 2024, utilizing the Sukoon Marriage Readiness Scale. Before KPP, participants were categorized as "Highly Ready for Marriage" (20%, 18 individuals), "Moderately Ready" (50%, 45 individuals), and "Not Ready" (30%, 26 individuals). After completing KPP, the "Highly Ready" group increased to 65% (58 individuals), "Moderately Ready" remained at 30% (27 individuals), and "Not Ready" decreased to 5% (4 individuals). Pearson correlation analysis showed a strong relationship between KPP and readiness (r = 0.842, p = 0.000). Gender had no significant effect (p > 0.05), indicating KPP's universal applicability. The study concludes that KPP significantly enhances couples' readiness for marriage, contributing 98.7% to their emotional and mental preparedness. Recommendations include adapting KPP modules to address modern couples’ needs and increase program efficacy.